Impact of agricultural water management interventions on upstream–downstream trade-offs in the upper Cauvery catchment, southern India: a modelling study - Wable, P. S.; Garg, K. K.; Nune, R.; Venkataradha, A.; Anantha K. H.; Srinivasan, V.; Ragab, R.; Rowan, J.; Keller, V.; Majumdar, P.; Rees, G.; Singh, R.; et al. (Wiley, 2022)
The Cauvery basin in southern India is experiencing transboundary issues due to increasing water demand. This study analysed water balance components and the impact of agricultural water management (AWM) interventions in the upper Cauvery catchment of the Cauvery basin. Results showed that the study catchment receives an average of 1280 mm of annual rainfall. Of this, 29% (370 mm) flows downstream, 54% (700 mm) contributes to evapotranspiration (ET) and 17% (215 mm) contributes to groundwater recharge and surface storage. Rainfall varies from 700 to 5400 mm and the Western Ghats (mountain pass) are the main source of freshwater generation. The estimated ET in different catchments ranged from 500 to 900 mm per annum. An increase in the allocation of fresh water supplied by all three reservoirs (Hemavathi, Harangi and KRS) was observed in the canal command areas, from 1450 million cubic metres (MCM) yr‾¹ in 1971–1980 to 3800 MCM yr‾¹ in 2001–2010. AWM interventions harvested 140–160 MCM (13–20 mm) of surface runoff upstream of the upper Cauvery and reduced inflow into the Krishnaraja Sagar reservoir by 2–6%. The study findings are useful for designing and planning suitable water management interventions at basin scale.